Embryogenesis and Applications of Fingerprints- a review - Adamu, LH; Taura, MG (International Journal of Human Anatomy, 2017)
Fingerprint is an impression made by the friction ridges that are almost parallel at constant crest to crest wavelength. The pattern is dominated by central features, such as whorls, loops, arches and triradii. Fingerprints have been used for several decades in forensic and medical sciences. The fingerprints characteristics such uniqueness, consistency and universality are the main features that are used by forensic experts in identification processes, are well developed during intra-uterine life. Understanding embryogenesis of fingerprints is essential in linking its features to some disease conditions. The purpose of this review was to highlight information regarding establishment, formation, hypotheses and factors affecting fingerprints. Applications of the fingerprints in forensic and medical sciences were also highlighted. Both environmental (in utero) and genetic factors have role to play in the formation of the fingerprints. The primary role of fingerprints is personal identification; these can be achieved through revealing sex, ethnicity, diet and lifestyle of an individual. In another perspective the fingerprints can be used as tools in diagnosis and ascertaining presence of disease conditions, however, this is population specific.
Keywords: Forensic Anatomy; fingerprints; embryogenesis; medical sciences